2014
DOI: 10.1016/j.clinph.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the effects of theta burst stimulation on motor cortical plasticity in healthy participants

Abstract: Objective Theta-burst stimulation (TBS) is a repetitive transcranial magnetic stimulation (TMS) protocol, capable of enhancing or suppressing the amplitude of contralateral motor-evoked potentials (MEP) for several minutes after stimulation over the primary motor cortex. Continuous TBS (cTBS) produces a long-term depression (LTD)-like reduction of cortical excitability. The purpose of this study was to assess the test–retest reproducibility of the effects of cTBS and to investigate which neurophysiologic marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 27 publications
6
57
0
Order By: Relevance
“…For example, Vernet et al (2013) have shown that the effects of theta-burst stimulation effects waver over time, indicating that additional factors, such as fluctuations in attention, emotional state and arousal, interact with the TMS-induced changes on cortical excitability levels over time (Schutter et al, 2001;Vernet et al, 2013Vernet et al, , 2014Monte-Silva et al, 2009). Such oscillating patterns are also seen in some PAS studies (Grundey et al, 2012a;Kuo et al, 2007;Nitsche et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…For example, Vernet et al (2013) have shown that the effects of theta-burst stimulation effects waver over time, indicating that additional factors, such as fluctuations in attention, emotional state and arousal, interact with the TMS-induced changes on cortical excitability levels over time (Schutter et al, 2001;Vernet et al, 2013Vernet et al, , 2014Monte-Silva et al, 2009). Such oscillating patterns are also seen in some PAS studies (Grundey et al, 2012a;Kuo et al, 2007;Nitsche et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…It may be the case that choosing certain time points instead of the whole dataset can improve the sensitivity or robustness of the cluster analysis. One option may be to choose T5, previously found to be the most reliable time point for measuring MEP changes following cTBS (Vernet et al, 2014) and/or T10 to capture the peak effect of TBS, including for participants whose MEPs return rapidly to baseline levels, and perhaps one of the later time points, e.g., T40 and/or T50, to use their discriminatory power for classifying the cTBS aftereffects (present results) and for capturing the differential time of return of post-TBS MEP amplitudes to baseline levels between healthy and clinical populations (Oberman et al, 2010, 2012, 2014, 2016; Freitas et al, 2011b; McClintock et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The intensity was fixed at 80% of AMT. This paradigm was recently shown to induce significant suppression of MEPs in healthy controls (see Vernet et al, 2014). Before cTBS, two to three batches of 20 to 30 MEPs (60 in total) were acquired in response to stimulation over the optimal FDI location, at an intensity of 120% of RMT and a rate of approximately 0.1 Hz (a random jitter of ±1 s was introduced to avoid any training effects).…”
Section: Methodsmentioning
confidence: 99%